Color Doppler ultrasound and arteriovenous fistulas for hemodialysis - Zamboli, Pasquale; Fiorini, Fulvio; D’Amelio, Alessandro; Fatuzzo, Pasquale; Granata, Antonio (Journal of ultrasound, 2014)
Native arteriovenous fistula (AVF) is the vascular access of choice for hemodialysis patients. Compared with grafts and central venous catheters, AVFs last longer and are associated with fewer complications. The widespread use of the Doppler ultrasound (DUS) has increased the number of patients who are eligible for AVF by facilitating the identification of vessels that are suitable for fistula construction (preoperative vascular mapping). DUS can also extend native AVF survival by improving the early detection of complications (post-operative surveillance). It is the only imaging modality that furnishes both morphological and functional data on the native vascular access, and it is also the only imaging tool that can be used directly by the surgeon, an indisputable advantage. This review examines the numerous roles played by DUS in the construction and postoperative follow-up of AVFs, including preoperative vascular mapping, AVF maturation, and surveillance.